Determining Flood Protection Strategy with Uncertain Parameter Using Adjustable Robust Counterpart Methodology - Chaerani, Diah; Robbi, Muttaqien Rodhiya; Hertini, Elis; Rusyaman, Endang; Paulus, Erick (Jurnal ILMU DASAR, 2020)
Flooding is a natural disaster that often occurs, it is not surprising that floods are one of the problems that must be resolved in various countries, one of which is Indonesia. Flood is very detrimental to the public because the impact could be the loss of material and non-material. A flood protection system is needed and must be managed properly. This aims in management of flood protection systems often requires efficient cost control strategies that are the lowest possible long-term costs, but still meets the flood protection standards imposed by regulators in all plans. In this paper a flood protection strategy is modeled using Adjustable Robust Optimization. In this approach, there are two kinds of variables that must be decided, i.e., adjustable and non-adjustable variables. A numerical simulation is presented using Scilab Software. Keywords: Flood Protection Strategy, Uncertainty, Adjustable Robust Optimization, Scilab Software.